Persistence and distribution of dinotefuran in tree of heaven - Keyzer, Justin; Lewis, Phillip; McCullough, Deborah G. (Frontiers in Insect Science, 2023)
Spotted lanternfly (SLF) (Lycorma delicatula (White)), an invasive planthopper discovered in Pennsylvania, USA in 2014, feeds for approximately six months by sucking phloem sap from trunks and limbs of tree-of-heaven, Ailanthus altissima, along with several native trees and woody vines. Basal trunk sprays of dinotefuran, a systemic neonicotinoid insecticide, are commonly used to reduce SLF densities and spread. Information on dinotefuran persistence and within-tree distribution can help identify optimal timing of annual basal trunk sprays to facilitate efficient use of available resources. We applied dinotefuran to 20 uninfested A. altissima trees in early April then periodically sampled foliage to monitor insecticide residues. Foliar dinotefuran residues averaged (SE) 7.81.1 and 6.31.2 in July and August, respectively, then dropped significantly to 2.60.5 ppm in September. In a second study, 20 A. altissima trees were similarly treated with dinotefuran basal trunk sprays in early June. Trees were felled to collect foliage and phloem samples from branches and the trunk in either mid-July or September. Foliar residues averaged 12.7±1.3 and 14.6±2.2 ppm in July and September, respectively. Residues were detected in phloem collected from below the spray line on trunks of seven trees felled in July, averaging 8.6±4.4 ppm and in samples from above the spray line of three trees, averaging 3.7±1.3 ppm. Dinotefuran was detected in phloem from below spray lines of seven trees felled in September, averaging 3.7±1.3 ppm. Dinotefuran was not detected in phloem collected in September from above the spray line nor any branches sampled in either July or September.